(untitled) - Evans, M. W. (Singapore, 2001)
It is well known that classical electrodynamics is riddled with internal inconsistencies springing from the fact that it is a linear, Abelian theory in which the potentials are unphysical. This volume offers a self-consistent hypothesis which removes some of these problems, as well as builds a framework on which linear and nonlinear optics are treated as a non-Abelian gauge field theory based on the emergence of the fundamental magnetizing field of radiation, the B(3) field.
Keywords: Electrodynamics,Quantum electrodynamics,Quantum theory,Điện động lực học,Điện động lực học lượng tử,Lý thuyết lượng tử.